The Life of Ideas during a Community-Based Innovation Contest - Gillier, Thomas; Buffart, Mickaël; Liger, Victor; Piat, Gerald (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
Few studies focus on how ideas circulate during community-based innovation contests. This research studies a contest employing two creativity methods: the hybrid and the speedstorming. Participants initially ideated individually, then ideated in pairs, and finally selected ideas for development. A novel research method that permits to track the “life” of ideas is settled. We found that final ideas are moderately original in comparison to the remainder of ideas submitted. We also found that participants did not reveal their most original ideas. Finally, we show that the final ideas were not co-created by the participants but came from solitary individuals.